Physical chemical analysis of the leaves of eucalyptus camaldulensis and its hydrolizate as a substrate in the production of xylitol (2018)
Eucalyptus is used as a source of renewable energy and the development of several products at industrial level; wasted leaves and branches whose content of lignocellulosic material can be converted into raw material product with specifi c applications, therefore, physicochemical analysis of leaves and its hydrolyzate was performed to determine the viability of the substrate in the production of xylitol, through biotechnological processes. Physicochemical parameters such as humidity, water activity (Aw), total soluble solids (° Brix), thermogravimetry (TGA), and infrared (IR FT) to the plant sample, and titratable acidity, pH, reducing sugars (DNS) were evaluated, ° Brix and infrared to hydrolysates, showing results led to the conclusion that the residual biomass Eucalyptus camaldulensis, is a potential substrate in the production of xylitol from biotechnological reduction of fermentable sugars such as D-xylose utilizing yeasts Candida.